Land Use Regulations, Migration and Rising House Price Dispersion in the U.S. - Wukuang Cun; M. Hashem Pesaran (Center for Economic Studies and ifo Institute (CESifo), 2018)
This paper develops a dynamic spatial equilibrium model of regional housing markets in which house prices are jointly determined with migration flows. Agents optimize period-by-period and decide whether to remain where they are or migrate to a new location at the start of each period. The gain from migration depends on the differences in incomes, housing and migration costs. The agent's optimal location choice and the resultant migration process is shown to be Markovian with the transition probabilities across all location pairs given as non-linear functions of income and housing cost differentials, which are endogenously determined. On the supply side, in each location the construction firms build new houses by combing land and residential structures. The regional land supplies are exogenously given. When a tightening of regional land-use regulation reduces local housing supply, upward pressure on house prices created by excess housing demand cascades to other locations via migration. It is shown that the deterministic version of the model has a unique equilibrium and a unique balanced growth path. We estimate the state-level supplies of new residential land from the model using housing market and urban land acreage data. These estimates are shown to be significantly negatively correlated with the Wharton Residential Land Use Regulatory Index. The model can simultaneously account for the rise in house price dispersion and the interstate migration in the U.S. during the period 1976-2014. Counterfactual simulations suggest that reducing either land supply differentials or migration costs could significantly lower house price dispersion. The model predicts substantially smaller impacts of land-use deregulation on population reallocation as compared to recent existing models of housing and migration that assume population are perfectly mobile.
Keywords: E00; R23; R31; 330; house price dispersion; endogenous location choice; interstate migration; land-use restriction; spatial equilibrium